Warrior of the Altaii [compact disc, unabridged] - Jordan, Robert, 1948-2007 (Macmillan Audio, 2019)
The watering holes of the Plain are drying up, the fearsome fanghorn grow more numerous, and bad omens abound. Wulfgar, a leader of the Altaii people, must contend with twin queens, warlords, prophets, and magic in hopes of protecting his people and securing their future. Elspeth, a visitor from another world, holds the answers, but first Wulfgar must learn to ask the right questions. But what if the knowledge that saves the Altaii will also destroy them?